2019
DOI: 10.22434/ifamr2018.0102
|View full text |Cite
|
Sign up to set email alerts
|

Do traditional market consumers care about the halal meat label? A case study in Taiwan

Abstract: The majority of Taiwanese consumers are not familiar with halal food, although the halal diet has been a global trend highlighting three attributes: cleanliness, animal welfare, and religious norms. This study explores the purchase intention of traditional market consumers in buying halal-labeled chicken measured by their willingness-to-pay (WTP). A total of 904 valid survey samples were collected in May 2017. A logit model and interval regression analysis are adopted to analyze the purchase intention and to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Many other authors also explored the impact of religiosity on buying intention (Hussain et al, 2016;Khan and Azam, 2016;Awan et al, 2015;Jamal and Sharifuddin, 2015). Despite the fact that researchers have studied the relationship between religiosity and halal products, most have narrowly focussed on halal meat (Bonne et al, 2006(Bonne et al, , 2007Mahbubi et al, 2019;Yang, 2019). The idea of halal brands is comprehensive and goes beyond meat products.…”
Section: Influence Of Religiosity On Buying Intentions and Theory Of Planned Behaviour Antecedentsmentioning
confidence: 99%
“…Many other authors also explored the impact of religiosity on buying intention (Hussain et al, 2016;Khan and Azam, 2016;Awan et al, 2015;Jamal and Sharifuddin, 2015). Despite the fact that researchers have studied the relationship between religiosity and halal products, most have narrowly focussed on halal meat (Bonne et al, 2006(Bonne et al, , 2007Mahbubi et al, 2019;Yang, 2019). The idea of halal brands is comprehensive and goes beyond meat products.…”
Section: Influence Of Religiosity On Buying Intentions and Theory Of Planned Behaviour Antecedentsmentioning
confidence: 99%
“…Future studies are needed to compare the importance of health-related factors in shaping the behaviour of Muslim and non-Muslim customers towards halal food. Furthermore, we recommend future studies to investigate the influence of health-related factors on other behaviours such as loyalty and willingness to pay. Although Yang (2019), Jalil et al (2018); and Rezai et al (2010) have shown the significant influences of demographic factors on customer behaviour towards halal food, their influences rarely have been controlled in the previous studies which can influence the accuracy of the results. We recommend that future studies consider demographic factors such as age, gender, income and education as control variables. In comparison to cognitive factors, the potential influences of emotional factors on behaviour towards halal food have been rarely considered.…”
Section: Discussion: Research Gaps and Future Research Directionsmentioning
confidence: 99%
“…The agriculture sector of Taiwan has faced an enormous change in recent years. The reasons for such changes include the necessary response to economic downturns, fitting new employment requirements in agriculture sector, re-positioning for global competitiveness, new consumer's living concepts and trends, and the need for a technological upgrade to increase efficiency and effectiveness beyond traditional ways (Han and Hou, 2016;Lin, 2019;Su, and Wu, 2015;Yang, 2019). It has also been seen that there was a major pressure as a result of rapid economic development and increasing labor costs in recent decades (Ka, 2018).…”
Section: Types Of Agricultural Production In Taiwan and Consumption Levelmentioning
confidence: 99%